Kinetics of the thermolysis of 3‐nitro‐2, 4‐dihydro‐3H‐1, 2, 4‐triazol‐5‐one (NTO) and nanosize NTO the presence of nickel‐zinc‐cobalt ferrite. Issue 11 (9th August 2022) - Dave, Pragnesh N.; Sirach, Ruksana; Chaturvedi, Shalini
Abstract: This study deals with the evaluation of the catalytic activity of quaternary nickel‐zinc‐cobalt ferrite (NiZnCoF) nanoparticles on the thermal decomposition of 3‐nitro‐2, 4‐dihydro‐3H‐1, 2, 4‐triazol‐5‐one (NTO). Nanosize NiZnCoF has been successfully synthesized using the co‐precipitation method. The effect of 5% by mass NiZnCoF on the thermolysis of NTO and NTO with nanosize (nNTO) has been studied using simultaneous thermal analysis. In the presence of NiZnCoF additive, the decomposition of NTO and nNTO was increased by 8.55 and 7.68°C, indicating that the additive stabilizes NTO and nNTO. The DSC peak temperature also suggests the presence of NiZnCoF decreases the nNTO's exothermic curve by 5.62°C. The DSC peak curve of NTO in the presence of NiZnCoF was shifted from 276.35 to 272°C. The activation energy calculations suggested that the high activation energy of NTO can be reduced ∼82–87 kJ mol −1 by nanosizing NTO followed by the incorporation of NiZnCoF.